Analysis Of The Influence Of Customer Experience And Store Atmosphere On Customer Satisfaction At Nyctophily Coffee - Egga Arimbi Rudyta Klintan Sekarwangi; Mellasanti Ayuwardani (International Journal of Economics, Business and Innovation Research, 2023)
The increasingly modern lifestyle of society has led to diverse consumer desires and demands for products or services. One industry whose production has increased very rapidly in recent years is the coffee commodity. The purpose of this study was to analyze the effect of customer experience and store atmosphere on customer satisfaction at Nyctophily Coffee. This study uses accidental sampling method with 100 respondents as samples. The data collection methods used are questionnaires, literature study and observation. From the results of multiple linear regression analysis, the equation Y = 0.546 + 0.252X1 + 0.205X2 is obtained. The customer experience variable has a greater influence than the store atmosphere. The t test results show that customer experience and store atmosphere individually affect customer satisfaction. The coefficient of determination in this study is 0.417, which means that customer experience and store atmosphere contribute to customer satisfaction by 41.7% and 58.3% is influenced by other variables not examined in this study.